Ground-based infrared measurements of tropospheric source gases over Antarctica during the 1986 austral spring - Toon, G. C.; Farmer, C. B.; Schaper, P. W.; Blavier, J.-F.; Lowes, L. L. (1989)
Simultaneous measurements of the atmospheric burdens of CH4, N2O, CO2, CF2Cl2, and CO above McMurdo Station, Antarctica, have been derived from solar absorption spectra obtained by the Jet Propulsion Laboratory high-resolution Fourier transform spectrometer. In all cases the burdens are smaller than midlatitude values. Furthermore, retrievals of N2O and CH4 indicate that the tropospheric mixing ratios were normal and that the depletion of the burdens can best be accounted for by a downward shift of the volume mixing ratio profiles by some 6-8 km. This rules out the possibility of large-scale upwelling of ozone-poor tropospheric air into the stratosphere being the cause of the Antarctic springtime ozone depletion.